Industry Determinants of Organizational Culture - Gordon, George G. (Academy of Management Review, 1991)
This article develops the argument that organizational or corporate culture is strongly influenced by the characteristics of the industry in which the company operates. Thus, companies within an industry share certain cultural elements that are required for survival. The article identifies three classes of industry variables that have the potential for creating industry-driven cultural elements: competitive environment, customer requirements, and societal expectations. The article also discusses implications of the industry influences on the potential for culture change.